Competitive and Cooperative Adsorption of Aromatic Acids and Bases onto a New Aminated Macroreticular Adsorbent - Wei-Ming Zhang; Jin-Long Chen; Bing-Cai Pan; Quan-Xing Zhang (Adsorption Science & Technology)
The adsorption behaviour of three aromatic acids [phenol, benzoic acid (BCA) and 2-naphthalene sulphonic acid (2-NSA)] and of one aromatic base (aniline) on an aminated macroreticular adsorbent (NDA103) were investigated employing single or binary batch systems at 293 K and 313 K, respectively. All the adsorption isotherms in the studied systems could be adequately fitted by the Langmuir model, thereby indicating the existence of an exothermic adsorption process for phenol, BCA and aniline. At low equilibrium concentrations, the individual uptakes in the single-component systems were higher than those in binary-component systems because of competition between the two types of adsorbate molecules towards the adsorption sites. On the other hand, it is noteworthy that the total molar uptakes of adsorbates in the binary-component systems at high equilibrium concentrations were larger than the uptakes in the single-component systems. In binary-component systems, a large excess of aromatic acids was noted on the adsorbent surface at saturation, presumably as a result of a cooperative effect arising primarily from acid–base interaction between the loaded adsorbates.